Sustainable Environment and Military Expenses: The Role of Energy Innovations - Isiksal, Aliya Zhakanova; Assi, Ala Fathi; Rakhmetullina, Shynar Zhakanovna; Zhakanov, Alibek (Journal of Environmental Accounting and Management, 2026)
This study utilizes second-generation panel techniques to define the determinants of emissions in the G7 region during the 1990-2018 period. The outcomes of the Pesaran and Yamagata and Pesaran CD techniques show that there is a correlation between the cross-sectional units and there is slope heterogeneity among states. This study employed static and dynamic techniques including the Mean Group (MG), Augmented Mean Group (AMG), and CS-ARDL approaches. In the long term, sustainable energy and environmental innovations reduce emissions, while it is augmented by economic expansion and military expenses. The outcomes of the Granger causality test indicated that military expenses cause economic expansion and economic expansion causes emissions. Moreover, sustainable energy and energy innovations affect emissions. Therefore, it is suggested that policymakers should implement eco-friendly strategies such as the distribution of eco-innovation and sustainable energy to promote sustainable development and protect the environment.